ASSESSING STUDENTS’ MISCONCEPTIONS ABOUT PURE SUBSTANCES, MIXTURES, AND SEPARATION OF MIXTURES USING A FOUR-TIER DIAGNOSTIC TEST (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2024)
Identifying misconceptions in students is essential to detect whether there are errors in students' understanding. Using a four-tier diagnostic test, the study surveyed students' knowledge of the matters among 121 junior high school students in grade VII. The results indicated that students have more misconceptions than scientific knowledge. Most students had misconceptions about chemical elements, compounds, and heterogeneous mixtures. These misconceptions could be due to students' limited ability to identify chemical elements, their inability to visualize heterogeneous mixtures at the submicroscopic level, and a mismatch of approaches that cause students' unfamiliarity with certain materials. Insights and suggestions to address students' misconceptions are discussed.
Keywords: assessing students' misconcesptions; four-tier diagnostic test